Community Informatics: Challenges in Bridging the Digital Divide - Peter, Songan; Khairuddin, Ab Hamid; Wee, Alvin Yeo; Jayapragas, Gnaniah; Hushairi, Zen (Universiti Malaysia Sarawak, 2008)
This paper describes how community informatics can help to overcome the digital divide between rural and urban communities in developing countries of Asia. The e-Bario project, a research initiative undertaken by a group of researchers from Universiti Malaysia Sarawak (UNIMAS) provides a context to demonstrate how information and communication technologies (ICTs) can provide opportunities for remote and rural communities to develop socially, culturally, and economically. The results of the initiative show the many ways in which ICTs can be used to improve the lives of the marginalized groups. However, other than the opportunities that the initiative provides, there are also many challenges that are encountered along the way. These challenges, based on the e-Bario experience are the major focus of this paper.